Meninjau Alasan “Tidak Dipenuhinya Kuota Domestic Market Obligation” Sebagai Dasar Pencabutan Izin Usaha Pertambangan Batubara - Priambudi, Zaki; Pambud, Bima Rico; Bahar, M. Ghifari Fardhana; Hidayat, Rivan (UI Scholars Hub, 2024)
The revocation of 2,078 Mining Business Licenses (IUP) on January 10, 2022, some of which was based on non-compliance with the Domestic Market Obligation (DMO) policy, is alleged to have been conducted arbitrarily, without regard for the principles and procedures of licensing management. Therefore, this research aims to analyze two legal issues: (1) Whether the revocation of the IUPs belonging to coal mining business entities that failed to meet the DMO quota by the Minister of Investment/Head of the Investment Coordinating Board (Head of BKPM) is a lawful decision; (2) What are the legal consequences of revoking the coal IUPs based on failure to meet the DMO quota on the agreements between the IUP holders and third parties? This research concludes that: (1) The decision to revoke the IUPs by the Head of BKPM is an unlawful decision and may be annulled. However, the revocation decision remains in effect as long as it has not been annulled by the competent authority and/or there is no final and binding court decision declaring the validity or invalidity of the decision. (2) The existence of a (relative) force majeure releases the IUP holder, as the debtor, from liability for breach of contract. This force majeure status is only temporary. If the debtor’s IUP is reinstated, the creditor may demand the fulfillment of the performance.